Quality of life for adult family caregivers of patients with dementia: a Systematic review - Aungsuroch, Yupin; Juanamasta, I Gede; Elsherbiny, Ola Ebrahim; Kabaya, Sonoko (Universitas Airlangga, 2024)
Introduction: to evaluate problems and factors related to quality of life (QoL) for adult family caregivers (FCGs) of patients with dementia. Methods: The study used a systematic review method with the guidelines of PRISMA 2020 and registered in PROSPERO CRD42023464726. The review focused on adult FCGs for people with dementia in the home setting. The literature was searched from four databases, including Scopus, Web of Science, CINAHL, and PubMed. This systematic review examined a subset of fifty-two out of a total of 2,263. The study used a narrative synthesis method to analyze the study. Results: The result showed that the severity of a patient with dementia's condition had an essential role in the patient's state. It impacted the caregiver's condition indirectly. Personal strategies (coping, resilience, sense of coherence, and expressed emotion) had an essential role in the caregiver situation. A maladaptive strategy would increase the stress of the caregivers and lead to a burden and depression. Those conditions of the caregiver would affect their QoL. Conclusions: Caring for patients with dementia is a huge psychological distress and burden on FCGs, which may negatively affect their quality of life in many aspects. Therefore, FCGs need education and support programs to maintain their overall aspect of quality of life and enable them to produce care for loved people.